Sympathectomy abrogates immunodeficiency associated with protein-energy malnutrition - González-Ariki, Silvia; Husband, Alan J (Journal of neuroimmunology, 1999)
The role of the sympathetic nervous system in the immune deficiency developed in protein-energy malnutrition (PEM) was investigated by assessing the effects of sympathectomy on the intestinal immune response of rats subject to prenatal or postnatal malnutrition. Chemical sympathectomy increased the number of IgA+ cells migrating into the intestinal lamina propria of control animals, but this effect was abrogated in rats malnourished during their perinatal stage. The method by which perinatal malnutrition was achieved influenced the magnitude of the effect on serum IgA levels with malnutrition during lactation having a more pronounced depressive effect on IgA than malnutrition during gestation. In experiments in which animals were intestinally immunised with ovalbumin (OVA) the mucosal immune response was reduced in non-sympathectomised malnourished (MN) animals and a lower level of anti-OVA IgA was detected in serum. However, in sympathectomised animals, there was no difference between MN animals and controls in the intestinal and humoral immune responses. The preliminary evidence presented in this paper strongly supports a role for the noradrenergic neurotransmitter system in the immunodeficiency developed during PEM.